Internal Limiting Membrane Flaps for Coexistent Macular Hole and Retinal Detachment in Eyes with Proliferative Diabetic Retinopathy. (6th November 2018) - Chen, San-Ni; Yang, Chung-May
Abstract : Purpose . To evaluate logical surgical approaches to closing macular holes in eyes with proliferative diabetic retinopathy with retinal detachment. Methods . Retrospective, interventional case series. Results . 10 eyes in 10 patients were included in this study. The inverted internal limiting membrane (ILM) flap technique was used in 2 eyes, while inverted ILM insertion was used in 5 eyes, and free ILM flaps in 3 eyes. Closed macular holes and retinal reattachment were observed in all eyes. Best corrected visual acuity improved from 1.33 ± 0.39 preoperatively to 1.02 ± 0.36 postoperatively (p = 0.03 ). Conclusion . Various surgical approaches utilized in managing macular holes may effectively close macular holes and reattach retinas. This trial is registered withNCT 03618498 .